Ursolic Acid Inhibits Adipogenesis in 3T3-L1 Adipocytes through LKB1/AMPK Pathway - He, Yonghan (Public Library of Science, 2013)
BACKGROUND: Ursolic acid (UA) is a triterpenoid compound with multiple biological functions. This compound has recently been reported to possess an anti-obesity effect; however, the mechanisms are less understood. OBJECTIVE: As adipogenesis plays a critical role in obesity, the present study was conducted to investigate the effect of UA on adipogenesis and mechanisms of action in 3T3-L1 preadipocytes. METHODS AND RESULTS: The 3T3-L1 preadipocytes were induced to differentiate in the presence or absence of UA for 6 days. The cells were determined for proliferation, differentiation, fat accumulation as well as the protein expressions of molecular targets that regulate or are involved in fatty acid synthesis and oxidation. The results demonstrated that ursolic acid at concentrations ranging from 2.5 µM to 10 µM dose-dependently attenuated adipogenesis, accompanied by reduced protein expression of CCAAT element binding protein β (C/EBP(β)), peroxisome proliferator-activated receptor γ (PPAR(γ)), CCAAT element binding protein α (C/EBP(α)) and sterol regulatory element binding protein 1c (SREBP-1c), respectively. Ursolic acid increased the phosphorylation of acetyl-CoA carboxylase (ACC) and protein expression of carnitine palmitoyltransferase 1 (CPT1), but decreased protein expression of fatty acid synthase (FAS) and fatty acid-binding protein 4 (FABP4). Ursolic acid increased the phosphorylation of AMP-activated protein kinase (AMPK) and protein expression of (silent mating type information regulation 2, homolog) 1 (Sirt1). Further studies demonstrated that the anti-adipogenic effect of UA was reversed by the AMPK siRNA, but not by the Sirt1 inhibitor nicotinamide. Liver kinase B1 (LKB1), the upstream kinase of AMPK, was upregulated by UA. When LKB1 was silenced with siRNA or the inhibitor radicicol, the effect of UA on AMPK activation was diminished. CONCLUSIONS: Ursolic acid inhibited 3T3-L1 preadipocyte differentiation and adipogenesis through the LKB1/AMPK pathway. There is potential to develop UA into a therapeutic agent for the prevention or treatment of obesity.